2015
DOI: 10.2478/jomb-2014-0044
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Thyroid Hormones, Lipids and Oxidative Stress Markers in Subclinical Hypothyroidism / Povezanost Izme\U Tireoidnih Hormona, Lipida I Markera Oksidativnog Stresa U SubkliniĉKoj Hipotireozi

Abstract: SummaryBackgroundOxidative stress plays a role in the pathogenesis of many chronic diseases. It is recognized in overt hypothyroidism while its existence in subclinical hypothyroidism (SCH) is not well established. The aim of this study was to determine whether there was increased oxidation of lipids and proteins in SCH, and examine their association with lipids and thyroid hormones.MethodsMale adults (35–59 years) with SCH (n=467) and euthyroid controls (n=190) were studied. Anthropometric measurements, plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 34 publications
(47 reference statements)
2
6
2
1
Order By: Relevance
“…Inter-individual variations are particularly high for the serum concentration of Tg, because there are differences in the weight of the thyroid gland in different individuals, the status of TSH, and there are also conditions associated with thyroid injury (thyroiditis) – all of these conditions are affected by the serum concentration of Tg ( 31 ). Although there is statistically significant difference in the values of TSH and fT3 between different age groups ( Table II ), we cannot say that our study is consistent with the results of other studies ( 35 – 37 ) in which the levels of TSH and free T3 gradually declined in older age. When we analyzed the TSH and T4 levels in the male and female population, we found no statistically significant difference between these two groups, but for the fT4, T3 and fT3 values we found significant difference ( Table III ).…”
Section: Discussioncontrasting
confidence: 59%
“…Inter-individual variations are particularly high for the serum concentration of Tg, because there are differences in the weight of the thyroid gland in different individuals, the status of TSH, and there are also conditions associated with thyroid injury (thyroiditis) – all of these conditions are affected by the serum concentration of Tg ( 31 ). Although there is statistically significant difference in the values of TSH and fT3 between different age groups ( Table II ), we cannot say that our study is consistent with the results of other studies ( 35 – 37 ) in which the levels of TSH and free T3 gradually declined in older age. When we analyzed the TSH and T4 levels in the male and female population, we found no statistically significant difference between these two groups, but for the fT4, T3 and fT3 values we found significant difference ( Table III ).…”
Section: Discussioncontrasting
confidence: 59%
“…Oxidative stress is strongly linked to inflammation with several reports demonstrated significant increase in oxidation stress in children with obesity that plays a key role in the development of obesity complications [24]. Several studies reported higher oxidative stress in subjects with subclinical hypothyroidism [25]. However, our study showed no significant difference in oxidative DNA damage between obese and normal weight children with no significant association between 8-hydroxydeoxyguanosine and subclinical hypothyroidism.…”
Section: Discussioncontrasting
confidence: 69%
“…However, persistent hyperlipidemia can lead to antioxidant system overload and, subsequently, to a decrease in the level of antioxidant defense. As a consequence, with progressive hyperlipidemia, oxidative stress increases, which is observed in subclinical hypothyroidism (Yang et al, 2008;Cheserek et al, 2015). The effect is confirmed by a significant correlation between MDA and LDL-cholesterol levels, total cholesterol and triglycerides levels.…”
Section: Discussionmentioning
confidence: 85%
“…Perhaps the main role in the formation of malonic dialdehyde level in the experimental group was performed by specific lipid profile. Some authors believe that oxidative stress and MDA growth in hypothyroidism (both expressed and subclinical) are caused not by direct changes in thyroid status, but by changes in the lipid profile caused by thyroid dysfunction (Santi et al, 2012;Anjaneyulu et al, 2015;Cheserek et al, 2015). Prolonged availability of oxidative substrates (mainly low density lipoprotein cholesterol, LDL-C) in plasma increases their susceptibility to oxidative modification (Napoli et al, 1995).…”
Section: Discussionmentioning
confidence: 99%